2017
DOI: 10.1155/2017/3167985
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of GFP Reporter Gene Transduction and Expression on Metabolomics of Placental Mesenchymal Stem Cells Determined by UHPLC-Q/TOF-MS

Abstract: Introduction Green fluorescent protein (GFP) is widely used as a reporter gene in regenerative medicine research to label and track stem cells. Here, we examined whether expressing GFP gene may impact the metabolism of human placental mesenchymal stem cells (hPMSCs). Methods The GFP gene was transduced into hPMSCs using lentiviral-based infection to establish GFP+hPMSCs. A sensitive 13C/12C-dansyl labeling LC-MS method targeting the amine/phenol submetabolome was used for in-depth cell metabolome profiling. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…It is considered that EGFP gene functionally is neutral when integrated and provides convenient cell labeling without a significant impact on basic cellular functions [52], even within MSCs [53]. We demonstrated that within our isolated MSCs, transduction of AD-MSCs, BM-MSCs, and DP-MSCs cells by LV-EGFP did not lead to significant changes in the expression of the investigated markers, which is consistent with other works [54].…”
Section: Discussionsupporting
confidence: 91%
“…It is considered that EGFP gene functionally is neutral when integrated and provides convenient cell labeling without a significant impact on basic cellular functions [52], even within MSCs [53]. We demonstrated that within our isolated MSCs, transduction of AD-MSCs, BM-MSCs, and DP-MSCs cells by LV-EGFP did not lead to significant changes in the expression of the investigated markers, which is consistent with other works [54].…”
Section: Discussionsupporting
confidence: 91%
“…A number of prior studies have failed to identify any metabolic signature associated with the overexpression of a protein in a cell line. 42,43 A tree diagram (Figure 1F) derived from the score plot (Figure 1E DNAJA1 expression, indicating metabolome perturbations accumulated over time. However, the tree diagram indicates that the metabolome of WT-Bx cells did not change over time.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Our experimental results agree well with the previous report that GFP labelling has a negligible influence on cell metabolism. 51 Therefore, it is valid to use HCT116-GFP cells to represent HCT116 cells for the co-culture studies.…”
Section: Resultsmentioning
confidence: 99%
“…Stable HCT116-GFP cells, generated from HCT116 cells by lentiviral vector transduction, were purchased (Cellomics Technology, Halethorpe, MD, USA). Because GFP (green fluorescent protein) labeling has no significant influence on cell metabolism and functions, 51 HCT116-GFP cells are also defined as drug-sensitive cells in the current study. To maintain the ability of expressing the green fluorescent protein, HCT116-GFP cells were cultured in a complete growth medium containing 1 μg mL −1 puromycin.…”
Section: Experimental Methodsmentioning
confidence: 99%